In the shadows of interpretation: manipulative nature of translation in colliding of sacral and marginal - Garnyk, Liudmyla; Vitkovskyi, Yurii; AL-Khalavani, Khusameddin (Journal of Education Culture and Society, 2021)
Aim. Aim of the article is to provide critical examination of manipulation process as multidimensional phenomenon related to imagination, representation, translation and interpreting of original texts in light of assurance of informational safety that is our research object. Our research corresponds to theory and practice of translation, psychology, comparative religious studies, international relations, public diplomacy and national security. Methods. Research methodology is based on critical analysis of manipulations with texts; the methods have been borrowed from works of Gilbert Durand (1999), Michel Maffesoli (1996) and James Frazer (2012) on social anthropology. Results. Practical value of obtained results consists in proposed algorithm for critical analysis of translated or interpreted texts that allows to evaluate their quality according to context, meaning and semiotics of the source texts. The notion of empire as an archetype that was implemented into contemporary international relations is also revised and extended. That can help in analysis and prevention of different forms and means of outside and inside tactics of deviant influence on societies and to illuminate threats for cultural identity and spiritual diversity of the global community. Conclusions. Phenomenon of marginalization of cultural and spiritual identity (sacral sphere) under the influence of globalization by the means of soft power pressure can be evaluated today as the unspoken impact of influence agents implemented into new societal institutes in the form of alien cultural imperatives that are enforced to different communities as common for all agendas in the frameworks of postmodern stream.